Determination of Densities of Amino Compounds for Molar Volumes in Aqueous Solutions with Magnetic Float Densimeter at Various Temperatures - Singh, Man (Biological Sciences - PJSIR, 2006)
Densities (r) of urea (H NCONH ), methylurea (H C-HNCONH ), melamine (C N H ) in aqueous, alongwith 2 2 3 2 3 6 6 mehtylurea in 0.05 mol kg-1 aqueous urea solutions have been measured with magnetic float densimeter (MFD) with f f 2 the accuracy value of 1x10-3 kg m-3. The data were used to calculate apparent molar volumes (Vf ) that are compared with the values obtained with Anton Paar densimeter DMA 60/601 model. The values of the r and Vf parameters were regressed and extrapolated to zero concentration (m = 0), for their limiting densities (ro) and limiting molar volumes (V o) alongwith their respective slope values. The values of the ro and V oconstants elucidated the heteromolecular interactions of -NH 2 group, and it was noted that -NH in different chemical compounds influenced interactions with water, especially with 3 electron donating -CH group of methylurea.